Study on Nested-Structured Load Shedding Method of Thermal Power Stations Based on Output Fluctuations - Liping Wang; Minghao Liu; Boquan Wang; Jiajie Wu; Chuangang Li (Energies, 2017)
The balance of electric power and energy is important for designing power stations’ load distribution, capacity allocation, and future operation plans, and is thus of vital significance for power design and planning departments. In this paper, we analyzed the correlation between the output fluctuations of power stations and the load fluctuations of the power system in order to study the load change of the power system within a year/month/day, and the output variation amongst the power stations in operation. Reducing the output of hydropower stations or increasing the output of thermal power stations (TPS) could keep the monthly adjustment coefficient of the power system within a certain range, and thus balance the power system’s electric power and energy. The method for calculating the balance of electric power and energy of TPS is also improved. The nested-structured load shedding method (NSLSM), which is based on the calculation principle of the load shedding method, is put forward to iteratively calculate the peak shaving capacity and non-peak shaving capacity of every single thermal power station. In this way, the output process of each thermal power station can be obtained. According to the results and analysis of an example, the proposed methods of calculating monthly adjustment coefficients and the balance of electric power and energy of a thermal power station are validated in terms of correctness, feasibility, and effectiveness.